PENDAMPINGAN MANAJEMEN APLIKASI SIGIZI TERPADU UNTUK PELAPORAN STATUS GIZI DI UPTD PUSKESMAS NGASEM TAHUN 2025 - M Lutvi Irvan A.; Luluk S.; Aris Dwi C. (Suluh Adiluhung Publisher (SAPub), 2026)
The digitalization of health information systems represents a strategic move by the Ministry of Health of the Republic of Indonesia to enhance the accuracy of nutritional status data for children under five, thereby supporting decision-making for stunting prevention programs. This community service initiative aimed to analyze the implementation of the Sigizi Terpadu (Integrated Nutrition Information System) application and identify the causes of discrepancies in nutritional monitoring coverage calculations—comparing the manual Posyandu Recap (APR) application method with the digital Sigizi Terpadu system—at the Ngasem Community Health Center (Puskesmas) in Kediri Regency. A descriptive qualitative approach was employed, utilizing in-depth interviews with the health center's nutrition team, field observations, and root cause analysis via Fishbone (Ishikawa) diagrams. The analysis revealed significant differences in 2023 reporting figures: Sigizi Terpadu recorded a coverage rate of 53.7%, whereas the manual APR method showed 49.5%; notably, neither figure met the Health Office's target indicator of 86%. Key factors contributing to this discrepancy included the use of dummy National Identity Numbers (NIK) in the system, errors or bugs caused by surges in national user traffic, irregular attendance of children at Posyandu (disrupting N/D status tracking), limited variety in Supplementary Feeding (PMT) menus, and constraints on village funding. Implemented solutions included data cleaning, the standardization of reporting exclusively through Sigizi Terpadu starting in early 2025, and enhanced education for community health volunteers and parents.